Ubuntu: A Multidisciplinary Perspective to Understanding and Application - Simangele Mayisela; Roshini Pillay; Mzikazi Nduna; Fhumulani Mavis Mulaudzi; Rafiat Ajoke Anokwuru; Liepollo Ntlhakana; Mapula Jaqueline Mokwena; Takalani Rhoda Luhalima; Shonisani Agnes Mulovhedzi; Beatha Set; Rachel Shanyanana-Amaambo; Moses Chirimbana; et al. (AOSIS, 2026)
Ubuntu: A multidisciplinary perspective to understanding and application is a timely and significant contribution to contemporary African scholarship. This edited volume brings together a diverse group of scholars and practitioners who engage critically and creatively with Ubuntu as both a philosophical lens and a practical framework for transformation. Spanning multiple disciplines, the book demonstrates the enduring relevance of Ubuntu across varied social, educational and health contexts. Rather than presenting Ubuntu as a static cultural ideal, the chapters explore its evolving meaning and application in response to complex contemporary challenges. Themes such as digital mourning, feminist mentorship, tele-audiology, early childhood development and community care illustrate how Ubuntu informs inclusive practice, ethical leadership and socially responsive scholarship. Rooted in interconnectedness, compassion, dignity and solidarity, Ubuntu is positioned as a living and dynamic framework that shapes individual and collective responses to crisis, including the COVID-19 pandemic. The volume combines philosophical depth with thoughtful social critique, offering African-centred perspectives on justice, resilience and social cohesion in a rapidly changing world. This book will be of value especially to scholars, but also to postgraduate students and research-practitioners seeking rigorous, contextually grounded approaches to equity, healing and institutional transformation.